Beginners Approach to the Open Source Programming: Case Study Arduino with ESP32 - Bhadane, Pravin; Lal, Aparna (International Journal of Computer Sciences and Engineering, 2025)
Open source programming of arduino with case study of ESP32 has been studied. Open source programming is suitable for both students as well as for beginners. The basic concept of Open System Software (OSS), particularly its need, application and suitability for IoT has been studied with suitable example. One of the popular OSS platform i.e. Arduino is considered as a case study. Open source programming of Arduino for the beginners in the field of embedded system as well as IoT is carried out with the sample microcontroller ESP32. The reasons for popularity of ESP32 microcontroller, particularly integration of radio frequency module on its silicon chip, are discussed. It includes concept of open source programming, downloading and installation of open source Integrated development Environment (IDE) software, understanding of IDE functions, coding and finally burning of hex code into the flash memory of microcontroller. It also includes some technical insights of programming process. The present work is suitable for beginners as well as for new students in the field of electronics and computer science.